Incidence of an Aberrant Right Subclavian Artery on Second‐Trimester Sonography in an Unselected Population. (4th March 2017) - Gursoy Erzincan, Selen; Karamustafaoglu Balci, Burcin; Tokgoz, Cengiz; Kalelioglu, Ibrahim Halil
Abstract : Objectives: The aim of this study was to assess the incidence of an aberrant right subclavian artery (ARSA) among an unselected population during second‐trimester sonography and to review the importance of this conotruncal variant as a marker of Down syndrome. Methods: The presence or absence of an ARSA was assessed in an unselected population of 1913 second‐trimester fetuses. Results: Among the 1913 patients, an ARSA was detected in 20 fetuses (1.04%), all with a normal karyotype. Thirteen of 20 fetuses had an isolated ARSA, and 7 of them were nonisolated. Associated abnormal sonographic findings were an intracardiac echogenic focus (n = 3), a choroid plexus cyst (n = 1), pyelectasis (n = 1) and tetralogy of Fallot (n = 2). One of the cases of tetralogy of Fallot was also associated with a persistent left superior vena cava, a persistent right umbilical vein, hydrocephalus, rhombencephalosynapsis, and unilateral renal agenesis. There were only 2 fetuses with Down syndrome in this group, and both of them had a normal origin of the right subclavian artery. Conclusions: In an unselected population, an ARSA may be seen less frequently than in a high‐risk population and may not be related to Down syndrome. An isolated ARSA is not a sufficient indication for karyotype analysis; it can be managed with noninvasive prenatal testing rather than invasive testing.